Providing a Curriculum Design Pattern for Green Technical and Vocational Education of Secondary School in Iran - Baghbanpourasl, Laleh; Faghihi , Alireza; Seifi, Mohammad; Nateghi, Faezeh (Iranian Journal of Educational Sociology, 2022)
Purpose: The present study aims to identify factors affecting the design of green technical and vocational curriculum and provide a curriculum design pattern for green technical and vocational education of secondary school in Iran and its validation. Green technical and vocational training relies on issues such as environmental pollution reduction and creation of workforce for clean industries, such as the recycling industry. This type of training is based on the new labor market (green economy) that has been created to address the environmental problems of human industrial life in the present age. Method: In order to achieve the research objective, qualitative research method with an approach to grounded theory has been used. Twenty-five individuals have been selected from among all faculty members and experts in the fields of curriculum and environment through targeted sampling. Analysis of data gathered through open interviews has been done using coding. Findings: In the final analysis, the extracted concepts have been classified into 86 sub-categories and 17 themes or categories. Conclusion: According to the research results, the components that directly affect the implementation of green technical and vocational education curriculum of secondary school are identified and a favorable pattern is presented. Based on this, “design of green technical and vocational curriculum,” as the axial category, is realized based on the context of causal factors of “macro environmental policies,” “relationship with the green labor market linked to the green economy through modular principles” and internship standards through the principles of “teacher participation in the design of green curriculum” and “continuous engagement with scientific and research centers” taking into account “learners’ characteristics” and “professional qualifications required for green employment (as the background of the model).” Therefore, it will lead to the realization of “educational and economic consequences”.